The chromosome-level genome assembly of Prunus cerasifera ‘Atropurpurea’ - Hanlei Li; Linchang Dong; Mingjun Zhang; Jinrong Li; Yi Zheng; Qinghua Dong; Sen Wang (Scientific Data)
Abstract Prunus cerasifera ‘Atropurpurea’ (Purpleleaf Plum), known for its unique purple-red foliage, is an important ornamental plant that enhances the aesthetic value of urban greening. To explore the molecular mechanisms underlying leaf color changes, this study assembled the Purpleleaf Plum genome, providing new insights for related research. We used HiFi sequencing data to assemble its genome. After chromosome anchoring, the final genome size was 244.89 Mb, with a contig N50 of 26.60 Mb, and approximately 97.10% of sequences were anchored to 8 chromosomes. Genome annotation identified 28,231 protein-coding genes, with LTR transposons comprising 27.93% of the genome. BUSCO assessment revealed a genome completeness of 98.9%. Telomeric repeat analysis identified 14 telomeres, with six chromosomes capped by double telomeres and two chromosomes containing a single telomere. This high-quality Purpleleaf Plum genome provides a solid foundation for future gene function analysis, cultivar improvement, and genetic research, offering valuable resources for related fields.